Novel FREM1 mutations expand the phenotypic spectrum associated with manitoba‐oculo‐tricho‐anal (MOTA) syndrome and bifid nose renal agenesis anorectal malformations (BNAR) syndrome1. Issue 3 (8th February 2013) - Nathanson, Jared; Swarr, Daniel T.; Singer, Amihood; Liu, Mochi; Chinn, Amy; Jones, Wendy; Hurst, Jane; Khalek, Nahla; Zackai, Elaine; Slavotinek, Anne
Abstract Loss of function mutations in FREM1 have been demonstrated in Manitoba‐oculo‐tricho‐anal (MOTA) syndrome and Bifid Nose Renal Agenesis and Anorectal malformations (BNAR) syndrome, but the wider phenotypic spectrum that is associated with FREM1 mutations remains to be defined. We screened three probands with phenotypic features of MOTA syndrome. In one severely affected infant who was diagnosed with MOTA syndrome because of bilateral eyelid colobomas, a bifid nasal tip, hydrometrocolpos and vaginal atresia, we found two nonsense mutations that likely result in complete loss of FREM1 function. This infant also had renal dysplasia, a finding more consistent with BNAR syndrome. Another male who was homozygous for a novel stop mutation had an extensive eyelid colobomas, corneopalpebral synechiae, and unilateral renal agenesis. A third male child diagnosed with MOTA syndrome because of corneopalpebral synechiae and eyelid colobomas had a homozygous splice site mutation in FREM1. These cases illustrate that disruption of the FREM1 gene can produce a spectrum of clinical manifestations encompassing the previously described MOTA and BNAR syndromes, and that features of both syndromes may be seen in the same individual. The phenotype of FREM1‐related disorders is thus more pleiotropic than for MOTA and BNAR syndrome alone and more closely resembles the widespread clinical involvement seen with Fraser syndrome. Moreover, our first case demonstrates that vaginal atresia may be a feature of FREM1‐related disorders. © 2013 Wiley Periodicals, Inc.